2017
DOI: 10.1002/ccd.26939
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of periprocedural myocardial infarction after percutaneous coronary intervention: Analysis based on the SCAI definition

Abstract: Age, multivessel treatment, at least one bifurcation treatment, and total treated lesion length are predictive of PMI. The PMI score could help identify patients at high risk of PMI after PCI. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
6
1
1
Order By: Relevance
“…However, about 38.8% of patients undergoing elective PCI, sustain myocardial injury arising from the procedure itself, the extent of which is significant enough to alter prognosis and is also associated with increased subsequent mortality . A major complication of PCI is PCI‐related myocardial infarction (MI) . According to the Third Universal Definition of MI (2012), a cTn value elevation (>5 × 99th percentile URL) within 48 h of PCI (in patients with normal baseline values) is classified as PCI‐related MI (Type 4a).…”
Section: Introductionmentioning
confidence: 99%
“…However, about 38.8% of patients undergoing elective PCI, sustain myocardial injury arising from the procedure itself, the extent of which is significant enough to alter prognosis and is also associated with increased subsequent mortality . A major complication of PCI is PCI‐related myocardial infarction (MI) . According to the Third Universal Definition of MI (2012), a cTn value elevation (>5 × 99th percentile URL) within 48 h of PCI (in patients with normal baseline values) is classified as PCI‐related MI (Type 4a).…”
Section: Introductionmentioning
confidence: 99%
“…() argued that elderly patients tend to have more complex coronary anatomy and pathology, such as severe calcification and diffuse disease, which are unfavorable for PCI. Plaque volume in patients with PMI is significantly greater than in patients without PMI (Higuchi et al., ; Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, almost 44% of our sample had multivessel disease, which increased the chance of DCTP by 79%. Multivessel disease also increased the chance of PMI by 25% in Korea (Park et al., ), 54% in the US (Cai et al., ), and nearly 70% in China (Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Earlier studies reported the relationship between PMI and clinical factors such as lesion/stent length, bifurcation lesions, SYNTAX score, and left main disease. 7,9,12,13) However, the factors associated with PMI in contemporary elective PCI were not fully understood. Therefore, the aim of this study was to investigate the determinants of PMI in contemporary elective PCI.…”
mentioning
confidence: 99%